Assessment of Service Quality of Samgyeopsal SA Batasan in Quezon City: A Basis for Enhancement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The primary objective of this study is to evaluate the service quality of Samgyeopsal saBatasan, a restaurant located in Quezon City. Service quality is a multi-dimensional conceptthat reflects customers' overall evaluation of the superiority or inferiority of a service. It refersto the extent to which a service meets or exceeds customers' expectations in terms ofvarious attributes such as reliability, responsiveness, assurance, empathy, and tangibles. Anaccurate and comprehensive assessment of service quality is essential for service providersto develop effective strategies for improving service quality and enhancing customersatisfaction.The study utilized a survey questionnaire via Google Forms to assess the service quality ofSamgyeopsal Sa Batasan. The results of this study indicated that the assessment of servicequality at Samgyeopsal Sa Batasan yielded a total average mean of 3.37 for reliability, 3.37for responsiveness, 3.43 for assurance, 3.43 for empathy, and 3.25 for tangibles. Thesescores were interpreted as "Agree" suggesting that customers generally agreed that therestaurant met their expectations in these dimensions of service quality. For challengesencountered in Samgyeopsal sa Batasan, slow service is the highest rating with 27respondents, equivalent to 54%; unavailability of certain products or services and problemswith the equipment and overall atmosphere got 13 responses, equivalent to 26% and bothgot the 2nd rank. Next, none or no challenges encountered got 11 responses, equivalent to22%, and got the 3rd rank.The recommendations that the researchers will take to Samgyeopsal sa Batasan are to havefast and friendly communication and achieve all customer expectations in terms of foodquality and food service. Consider factors such as space, layout, and customer flow to avoidcompromising existing customers' comfort and experience. Ensure that the addition of newseating does not compromise the overall design and functionality of the restaurant.
Keywords: Business Administration